Diferensiasi Pendirian Perseroan Terbatas Pasca Berlakunya Undang-Undang Cipta Kerja - Andys Karismawan; M Saleh (SALAM: Jurnal Sosial dan Budaya Syar-i, 2021)
The dynamics in the development of Limited Liability Companies after the enactment of the Job Creation Act and also the government's efforts to increase or encourage the growth of Micro, Small and Medium Enterprises. In this case, the government through the Job Creation Act gave birth to a new concept related to Limited Liability Companies. Where the new concept related to the Limited Liability Company is stated in Article 153A of Law Number 11 of 2020 which states that a company with the criteria of micro and small businesses can be established by one person and established with a statement letter. In the regulation of Limited Liability Companies for Micro and Small Businesses in the Job Creation Act, it creates a legal conflict with the concept of a single establishment. Because without the elements of an agreement, these provisions create inconsistencies with the Limited Liability Company Law. These problems arise because the role of the Notary in the establishment of a Limited Liability Company for Micro and Small Business is eliminated. The researcher uses the normative research method and the type of descriptive research. The analysis is carried out by comparing the concept of the Company in the Company Law Number 40 of 2007 and the Limited Liability Company in the Job Creation Act with the concept of Single Member Limited Liability. The results of this analysis suggest that it is mandatory to make a statement on the establishment of a Limited Liability Company for Micro and Small Medium Enterprises using a notarial deed so that the validity of the statement letter can be used as perfect evidence, as well as a clause in the statement letter for the establishment of a Limited Liability Company for Micro and Small Medium Enterprises to accommodate all wishes of the sole founder. in accordance with the provisions of the Company Law.Keywords: Differentiation; Establishment; Limited Liability Company AbstrakDinamika dalam perkembangan Perseroan Terbatas pasca berlakunya Undang-Undang Cipta Kerja dan juga merupakan upaya pemerintah dalam meningkatkan atau mendorong poertumbuhan Usaha Mikro, Usaha Kecil, Usaha Menengah. Dalam hal ini, pemerintah melalui Undang-Undang Cipta kerja melahirkan konsep baru terkait Perseroan Terbatas. Dimana konsep baru terkait Perseroan Terbatas tersebut dituangkan dalam Pasal 153A Undang-Undang Nomor 11 tahun 2020 yang menyatakan Perseroan dengan kriteria usaha Mikro dan kecil dapat didirikan satu orang dan didirikan dengan surat pernyataan. Dalam pengaturan Perseroan Terbatas untuk Usaha Mikro dan Kecil dalam Undang-Undang Cipta Kerja menimbulkan konflik Hukum dengan konsep Pendirian tunggal. Karena tanpa adanya unsur Perjanjian, ketentuan tersebut menimbulkan Inkonsistensi dengan Undang-Undang Perseroan Terbatas. Permasalahan tersebut muncul karena dihilangkannya peran Notaris dalam Pendirian Perseroan Terbatas Usaha Mikro dan Kecil. Peneliti menggunakan metode Penelitian normatif serta tipe Penelitian deskriptif. Untuk analisis dilakukan dengan cara membandingkan antara konsep Perseroan dalam Undang-Undang Perseroan Nomor 40 tahun 2007 dan Perseroan Terbatas dalam Undang-Undang Cipta kerja dengan konsep Single Member Limited Liability. Hasil dari analisa ini menyarankan diwajibkannya pembuatan pernyataan Pendirian Perseroan Terbatas Usaha Mikro dan Kecil Menengah menggunakan akta notaris agar keabsahan dari surat pernyataan tersebut dapat dijadikan sebagai alat bukti yang sempurna, serta klausul surat pernyataan Pendirian Perseroan Terbatas Usaha Mikro dan Kecil Menengah mengakomodasi segala kehendak pendiri tunggal sesuai dengan ketentuan dalam Undang-Undang Perseroan.Kata Kunci: Diferensiasi; Pendirian; Perseroan Terbatas